Direct percutaneous endoscopic jejunostomy (DPEJ) and percutaneous endoscopic gastrostomy with jejunal extension (PEG-J) technical success and outcomes: Systematic review and meta-analysis - Deliwala, Smit S.; Chandan, Saurabh; Kumar, Anand; Mohan, Babu; Ponnapalli, Anoosha; Hussain, Murtaza S.; Kaushal, Sunil; Novak, Joshua; Chawla, Saurabh (Endoscopy International Open, 2022)
Background and study aims Endoscopic methods of delivering uninterrupted feeding to the jejunum include direct percutaneous endoscopic jejunostomy (DPEJ) or PEG with jejunal extension (PEG-J), validated from small individual studies. We aim to perform a meta-analysis to assess their effectiveness and safety in a variety of clinical scenarios.Methods Major databases were searched until June 2021. Efficacy outcomes included technical and clinical success, while safety outcomes included adverse events (AEs) and malfunction rates. We assessed heterogeneity using I2 and classic fail-safe to assess bias.Results 29 studies included 1874 patients (983 males and 809 females); mean age of 60 ± 19 years. Pooled technical and clinical success rates with DPEJ were 86.6 % (CI, 82.1–90.1, I2 73.1) and 96.9 % (CI, 95.0–98.0, I2 12.7). The pooled incidence of malfunction, major and minor AEs with DPEJ were 11 %, 5 %, and 15 %. Pooled technical and clinical success for PEG-J were 94.4 % (CI, 85.5–97.9, I2 33) and 98.7 % (CI, 95.5–99.6, I2 < 0.001). The pooled incidence of malfunction, major and minor AEs with DPEJ were 24 %, 1 %, and 25 %. Device-assisted DPEJ performed better in altered gastrointestinal anatomy. First and second attempts were 87.6 % and 90.2 %.Conclusions DPEJ and PEG-J are safe and effective procedures placed with high fidelity with comparable outcomes. DPEJ was associated with fewer tube malfunction and failure rates; however, it is technically more complex and not standardized, while PEG-J had higher placement rates. The use of balloon enteroscopy was found to enhance DPEJ performance.